Modelling for Uncertainties in Resistance for Jacket Platforms in Malaysia - Kurian, V.J. (2013)
Abstract: Structural design strength is based on characteristic values of basic random variables of resistance. The behaviour of these variables of strength may vary in such a way that they become unsafe during any time of their design life. The data for this study was collected from an ISO certified fabrication yard in Malaysia and was used to make statistical models. The collected data is based on jackets which were under construction at the yard. Statistical analysis of the data was performed, taking into account the mean, coefficient of variation and bias values. Initially basic random variables were analyzed and after their statistical parameters were found, the basic stresses were simulated based on ISO 19902 code equations. Finally recommendations are made for the statistical characteristics of the random variables to be used in this region for the reliability analysis for tubular members and joints for ultimate limit state design of jacket platforms in Malaysia. Keywords: Distributions, jacket platform, material resistance, modelling uncertainty, monte-carlo simulation